EFEK PEMBERIAN MONOSODIUM GLUTAMAT (MSG) DALAM PENINGKATAN PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - indra dwi agustin; Anis Sholihah; Anis Rosyidah (AGRONISMA, 2022)
Pakcoy (Brassica rapa L.) is one of the most widely cultivated horticultural plants and is characterized by wider, thicker, and greener stems and leaves than ordinary mustard greens. This study aims to determine the effect of different doses of monosodium glutamate (MSG) on the growth and yield of pakcoy plants. The design used was a simple randomized block design (RAK) consisting of five treatments of MSG doses including P0 (0 g/plant), P1 (5 g/plant), P2 (10 g/plant), P3 (15 g/plant). ), P4 (20 g/plant). The results showed that the administration of monosodium glutamate (MSG) had a significant effect on the growth and yield of pakcoy plants. P2 treatment (10 g/plant) was the best treatment with a plant height of 20.73 cm and produced an economical fresh weight of 183.69 g/plant.Keywords : Pakcoy, Monosodium Glutamate (MSG), Growth, Yield.